FORMULASI DAN EVALUASI MUTU SABUN PADAT DENGAN PENAMBAHAN EKSTRAK SERAI, DAUN SENGGANI, DAN KULIT JERUK SIAM: Formulation and evaluation of the quality of solid soap with the addition of leaves senggani, leaf extracts and siam orange skin - Dinda Ramadhani (PAKIS JOURNAL INSTITUTE, 2023)
Solid soap is a type of solid soap with the addition of lemongrass extract, senggani leaves and Siamese orange peel which is expected to increase the benefits of solid soap. The purpose of this study was to determine the process and formulation of making solid soap using the addition of lemongrass extract, senggani leaves and siam orange peel on the characteristics of soap. The research method used in this study is an experimental design study method using ANOVA. The treatment in this study was with the addition of 70grams: 30grams of senggani leaves (SS1), 60grams of lemongrass: 40grams of senggani leaves (SS2), 50grams of lemongrass: 50grams of senggani leaves (SS3), 70grams of lemongrass:30grams of Siamese orange peel (SS4), 60grams of lemongrass. :40gram Siamese orange peel (SS5), 50gram lemongrass :50gram Siamese orange peel (SS6). Parameters observed were water content test, vitamin C content, acidity pH. The results of the water content test are 17.51%, vitamin C content is 6.68%, the pH value is in accordance with SNI 3532-2016 with a pH value of 8-11, the organoleptic results of solid soap are on the parameters of color, aroma and texture with each the mean level of liking (6.2), (5,7), and (5,7).